Creatine supplementation and sprint training in cyclists: Metabolic and performance effects - Myburgh, K. H.; Bold, A.; Bellinger, B.; Wilson, G.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 1996)
This investigation determined if creatine supplementation (20 gm/day for 7 days) and creatine maintenance (2 gm/day) would attenuate muscle ATP loss associated with intense sprint training, and improve performance after sprint training. Effects were compared to a placebo group in a double-blind study. The following conclusions were reached. 1. The percentage of type IIB fibers modifies creatine effects. 2.Creatine supplementation and maintenance did not decrease ATP loss during intense sprint training. 3.Sprint training decreased plasma levels of products of adenine nucleotide degradation and improved 30 sec sprint performance. 4.Creatine supplementation and maintenance did not alter one-hour cycle distance. Implication. Creatine supplementation apparently has a differential effect depending upon the muscle characteristics of the individual. Performance effects are limited to short-term anaerobic activities.